A comparison study of local dynamic stability measures of daily life walking in older adult community-dwelling fallers and non-fallers. Issue 9 (14th June 2016) - Ihlen, Espen A.F.; Weiss, Aner; Beck, Yoav; Helbostad, Jorunn L.; Hausdorff, Jeffrey M.
Abstract: In the present study we compared the performance of three different estimations of local dynamic stability λ to distinguish between the dynamics of the daily-life walking of elderly fallers and non-fallers. The study re-analyses inertial sensor data of 3-days daily-life activity originally described byWeiss et al. (2013) . The data set contains inertial sensor data from 39 older persons who reported less than 2 falls and 31 older persons who reported two or more falls the previous year. 3D-acceleration and 3D-velocity signals from walking epochs of 50 s were used to reconstruct a state space using three different methods. Local dynamic stability was estimated with the algorithms proposed byRosenstein et al. (1993), Kantz (1994), andIhlen et al. (2012a) . Median λ s assessed by Ihlen׳s and Kantz׳ algorithms discriminated better between elderly fallers and non-fallers (highest AUC=0.75 and 0.73) than Rosenstein׳s algorithm (highest AUC=0.59). The present results suggest that the ability of λ to distinguish between fallers and non-fallers is dependent on the parameter setting of the chosen algorithm. Further replication in larger samples of community-dwelling older persons and different patient groups is necessary before including the suggested parameter settings in fall risk assessment and prediction models.